Assessment of the left ventricular function in patients with uremia using layer-specific 2-dimensional speckle tracking echocardiography. Issue 9 (March 2019) - Sun, Mengyao; Dong, Yu; Wang, Ying; Li, Guangsen; Huang, Dongmei
Abstract : Abstract: The aim of this research is to evaluate the longitudinal and circumferential systolic function of the left ventricle with different configurations from endocardium, midmyocardium, and epicardium, respectively, in patients with uremia using layer-specific 2-dimensional speckle tracking echocardiography (2D-STE). According to the different left ventricular (LV) configurations, 119 patients with uremia were divided into 2 groups: LV normal group (LVN group, n = 63) and LV hypertrophy group (LVH group, n = 56). In all, 66 healthy volunteers were selected as controls. High-frame rate 2-dimensional images were recorded from the apical 4-chamber view, apical 2-chamber view, parasternal LV long-axis view, and mitral annulus, papillary muscle, and apical levels of the parasternal LV short-axis view during 3 consecutive cardiac cycles. The peak systolic longitudinal strain (LS) and circumferential strain (CS) were measured in the endocardium, midmyocardium, and epicardium. In the 3 groups, the endocardium had the highest LS and CS, whereas the epicardium had the lowest LS and CS; the LS and CS of each group gradually decreased from the endocardium to the epicardium in all the 3 sections; the LS and CS of the myocardial layers were kept gradient features, namely, endocardium > midmyocardium > epicardium. The LS of the endocardium in the LVN and LVH groups was significantly lower than that in the control group ( P  < .05). The LS of the midmyocardium and epicardium in the LVH group were significantly lower than those in the control group ( P  < .05). The LS of the endocardium significantly decreased in the LVH group compared with that in the LVN group ( P  < .05). The CS of the endocardium and midmyocardium in the LVH group significantly decreased compared with those in the control and LVN groups ( P  < .05). There were no significant differences in the CS between the LVN and control groups ( P  > .05). In patients with uremia, the longitudinal and circumferential systolic function in 3 myocardial layers of the LVH group, and the longitudinal systolic function in endocardium of the LVN group were found significantly impaired by layer-specific 2D-STE.